2017
DOI: 10.1590/1980-5918.030.004.ao09
|View full text |Cite
|
Sign up to set email alerts
|

The spasticity in the motor and functional disability in adults with post-stroke hemiparetic

Abstract: Introduction: Spasticity acts as a limiting factor in motor and functional recovery after Stroke, impairing the performance of daily living activities. Objective: To analyze the influence of spasticity on main muscle groups and to associate it with motor impairment and functional level of chronic hemiparetic patients after stroke. Methods: Twenty-seven chronic hemiparetic patients of both sexes were selected at the Physical Therapy and Occupational Therapy Service of the Unicamp Clinics Hospital. Assessments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
3
1
1
Order By: Relevance
“…Description of spasticity and its clinical implications are still having lack of attention. The prevalence of PSS in initial studies was approximately 60%; 13 however, current studies show lower rates of spasticity in 7-42% of post-stroke patients.…”
Section: Discussioncontrasting
confidence: 52%
“…Description of spasticity and its clinical implications are still having lack of attention. The prevalence of PSS in initial studies was approximately 60%; 13 however, current studies show lower rates of spasticity in 7-42% of post-stroke patients.…”
Section: Discussioncontrasting
confidence: 52%
“…Lin et al 50 found strong reverse correlation between the grade of spasticity and the hand functions in 10 individuals suffered from spasticity and hemiplegia after stroke. A cross-sectional study performed by Cacho et al 51 examined the relationship between spasticity and limb functionality, evaluating 27 patients, finding a negative correlation between upper limb spasticity and functional impairment but not lower limb. The authors proposed that the actual influence of spasticity on functional impairment was hard to measure because the level of spasticity may change according to the position of the limb or the task being performed.…”
Section: Discussionmentioning
confidence: 99%
“…After a stroke, motor unit control of the affected muscles may be lost (weakness) and voluntary muscle activation changes cause co-contraction of antagonist muscles and decreased activation of agonist muscles (Chae et al, 2002). Spasticity acts as a limiting factor to achieving upper extremity motor and functional recovery (Cacho et al, 2017). However, there were difficulties measuring the definite influence of spasticity on motor impairment after a stroke, as the level of spasticity may differ according to the task demands (Sommerfeld et al, 2004).…”
Section: Discussionmentioning
confidence: 99%